Honduras : Fifth and Sixth Reviews Under the Stand-By Arrangement-Press Release; Staff Report; and Statement by the Executive Director for Honduras. (IMF Staff Country Reports; Country Report ;, 2017)
This paper discusses Honduras' Fifth and Sixth Reviews under the Stand-by Arrangement (SBA). All continuous performance criteria for the end of June 2017 were met. The indicative target on the National Electricity Company's (ENEE) operating revenue-to-spending ratio was missed by a small margin owing to up-front fees paid to the loss-recovery concessionaire. On the structural front, notable reforms are the adoption of a fiscal responsibility law to anchor a sustainable medium-term fiscal position; the overhaul of the tax administration; and the reduction in the heavily overstaffed payroll of ENEE. The authorities have indicated that they will not purchase the amount available on completion of these reviews, in line with their intention to treat the SBA as precautionary.